1965
DOI: 10.1139/v65-224
|View full text |Cite
|
Sign up to set email alerts
|

The SYNTHESIS OF Α-Monofluoroalkanoic ACIDS

Abstract: a-Monofluoroalkanoic acids are important intermediates in the synthesis of biologically active fluorine compounds. General methods of preparation have been examined, based on the three following reagents: (a) hydrogen fluoride + N-bromoacetamide; (b) diethyl monofluoromalonate; and (c) perchloryl fluoride. The first of these is the recommended procedure for simple unsubstituted a-fluoro acids; however, the fluoromalonate route is less vigorous, and is therefore the method of choice for those a-fluoro acids tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1967
1967
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…FMA was prepared by two different synthetic routes (Figure 1) (Pattison et al, 1965). The first route (i) involved the fluorobromination of 1-tetradecene to yield l-bromo-2fluorotetradecane (5).…”
Section: Resultsmentioning
confidence: 99%
“…FMA was prepared by two different synthetic routes (Figure 1) (Pattison et al, 1965). The first route (i) involved the fluorobromination of 1-tetradecene to yield l-bromo-2fluorotetradecane (5).…”
Section: Resultsmentioning
confidence: 99%
“…The consequences of these factors, among others, lead to variable fluorine effects that have been described . For example, while the fluoromalonate anion was believed to be a weaker nucleophile than malonate in the reaction with alkyl bromides, the conjugate addition of α‐fluorodinitromethide anion to methyl acrylate in water is about 2000 times faster than that of α‐chlorodinitromethide or α‐alkyldinitromethide . Seminal work by Hu and co‐workers showed that α‐fluorodi(benzenesulfonyl)methane, (PhSO 2 ) 2 CFH, reacts with enones faster than di(benzenesulfonyl)methane, (PhSO 2 ) 2 CH 2 .…”
Section: Figurementioning
confidence: 99%
“…The fluoroacids were synthesized according to the method of Pattison et al (10,11) but yields on large scale preparations were poor especially for the branched-chain acid. Microanalyses were obtained from Schwarzkopf Microanalytical Laboratory, Woodside, New York.…”
Section: Ch3(ch2)4-ch-ch-(ch2)4ch3mentioning
confidence: 99%